Combined liver-kidney transplant: a single centre experience - Singh, Kailash N.; Grover, Ankit; Goyal, Neerav; Guleria, Sandeep (International Journal of Research in Medical Sciences, 2026)
Background: End-stage liver disease (ESLD) often coexists with chronic kidney disease (CKD), creating a need for combined liver-kidney transplantation (CLKT). While widely practiced in the West, Indian experience is limited. Aim was to evaluate the demographic profile, etiologies, peri-operative complications, and short-term in-hospital outcomes of patients undergoing CLKT. Methods: We retrospectively reviewed adults (>18 years) who underwent CLKT at our centre from January 2019 to February 2025. Records were analysed for demographics, etiology, peri-operative complications and outcomes. CKD was diagnosed by clinical features, imaging, and renal biopsy where indicated; liver disease was confirmed with serology, autoimmune markers, and imaging. Results: Twenty-three patients underwent CLKT, including 16 males (69.5%). All received live-related donor grafts after regulatory approval. Diabetes (71%) and hypertension (60.8%) were frequent comorbidities. CKD etiology included diabetic kidney disease (60.8%), chronic interstitial nephritis (21.7%), primary hyperoxaluria (8.6%), and chronic glomerulonephritis (8.6%). Liver disease was attributed to non-alcoholic steatohepatitis (NASH) (52.1%), hepatitis B (21.7%), and hepatitis C (17.3%); two hyperoxaluria patients received liver grafts for enzyme deficiency despite structurally normal livers. Postoperative complications included bile leak in 6 patients (23%), bleeding in 1 (4.3%), and prolonged hospitalization in 7 (30.4%). One patient died of sepsis on day 25. At discharge, mean creatinine was 1.0±0.2 mg/dl and bilirubin 1.3±0.7 mg/dl. Conclusions: CLKT is feasible and safe in the Indian living-donor setting, with results comparable to international reports. Optimal outcomes require careful selection, thorough evaluation, and meticulous perioperative care. Establishing national registries and uniform CLKT guidelines will help standardize practice and ensure equitable allocation.